Following Endocrine-Disrupting Effects on Gene Expression in Xenopus laevis - Spirhanzlova, Petra; Leemans, Michelle; Demeneix, Barbara A; Fini, Jean-Baptiste (Cold Spring Harbor protocols, 2019)
Endocrine-disrupting chemicals (EDCs), found in all categories of chemicals, are suspected to be a cause of declining well-being and human health, both as single molecules and as mixtures. It is therefore necessary to develop high throughput methods to assess the endocrine-disrupting potential of multiple chemicals currently on the market that are as yet untested. An advantage of in vivo chemical screening is that it provides a full spectrum of physiological impacts exerted by a given chemical. is an ideal model organism to test thyroid axis disruption in vivo as thyroid hormones (THs) are highly conserved across vertebrates and orchestrate tadpole metamorphosis. In particular, NF stage 45 are most apt for in vivo screening as at this stage the tadpoles possess all the main elements of thyroid hormone signaling (thyroid receptors, deiodinases transporters) and are metabolically competent, while fitting into multiple well plates, allowing the use of small amounts of test chemicals. One way to assess the endocrine-disrupting potential of chemicals or mixtures thereof is to analyze gene expression in organisms after a short time exposure to the chemical(s). Here we describe a protocol using embryos to detect endocrine disruption of the thyroid axis by analysis of gene expression and an alternative protocol for fluorescence read-out using a transgenic GFP-expressing line. Taken together, these methods allow detection of subtle changes in TH signaling by EDCs that either activate or inhibit TH signaling in vivo.